2022
DOI: 10.1155/2022/8631284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Secondary Metabolites from Mexican Plants with Antifungal Activity against Pathogenic Candida Species

Abstract: In the last three decades, invasive fungal infections caused by Candida species have become an important public health problem, because they are associated with high rates of morbidity and mortality in immunocompromised and hospitalized patients. The diagnosis and treatment of candidiasis are difficult and usually inefficient. Accordingly, a diversity of available drugs, currently employed to attack candidiasis, frequently induce resistance in patients promoting toxicity due to long-term treatments. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…MIC is the lowest concentration at which no colour change occurs [ 63 , 64 ], whereas MBC is the lowest concentration at which no growth is seen on a petri dish [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…MIC is the lowest concentration at which no colour change occurs [ 63 , 64 ], whereas MBC is the lowest concentration at which no growth is seen on a petri dish [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In several experiments, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) showed that the overall shape, cytoplasmic homogeneity, and cell wall thickness of bacterial and fungal cells were significantly changed after D-limonene treatment. In addition, it includes increased cell membrane permeability, altered membrane potential, and decreased heat resistance; leakage of intracellular substances, such as proteins, lipids, and nucleic acids, was also observed and even cell lysis at high concentrations, which may be due to the lipophilic and hydrophobic properties of D-limonene that promote lipid solubilization in the plasma membrane [70,77,79,86,[110][111][112][113][114]. However, unlike bacteria, D-limonene affects ergosterol and β-1,3-glucan, which are unique to fungi.…”
Section: Antibiofilm Activity Of D-limonenementioning
confidence: 99%
“…was also observed and even cell lysis at high concentrations, which may be due to lipophilic and hydrophobic properties of D-limonene that promote lipid solubilization the plasma membrane [70,77,79,86,[110][111][112][113][114]. However, unlike bacteria, D-limonene affe ergosterol and β-1,3-glucan, which are unique to fungi.…”
Section: Antibiofilm Activity Of D-limonenementioning
confidence: 99%
See 1 more Smart Citation
“…MIC is the lowest concentration at which no colour change occurs [61,62], whereas MBC is the lowest concentration at which no growth is seen on a petri dish [63]. Values are the mean ± SE.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bacterici...mentioning
confidence: 99%